Synergies through entanglement. Commoning entering the Urban Governance Realm. - Vogel, Nina (TU Wien, 2017)
Cities are in a continuous state of becoming, where changing social, environmental and economic conditions intersect . An inherent challenge in planning is finding legitimate and sustainable responses to a plurality of societal challenges, needs and goals. Top-down and investor-led planning is confronted with co-/self-management and collective appropriation of urban resources. Two prevalent trends for urbanization, "smart-city" approaches and urban commons, are opposed and discussed. This paper considers these tendencies and presents a transformative planning approach to urban governance that combines traditional planning tools with urban commons and forms of co-development. The paper introduces a conceptual suggestion, DINE, that potentially challenges city ideals in planning with three parallel analytical spheres: a) Dynamic master plan, b) IN-between uses, and c) Emergent arrangements. Conceptualizing commoning in urban governance could promote democratic disputes and support the formation and maintenance of alternative local environments. The DINE governance model is introduced as a potential conceptual toolbox for different planning projects and actors.
Keywords: Stadtplanung; Planungstheorie; Planungskonzept; Planungsinstrument; Planungsmodell; Smart City